Raising baby by the book : the education of American mothers - Grant, Julia, 1953- (New Haven, Conn. : Yale University Press, 1998)
"In this study of the education of American mothers, Julia Grant shows how the tides of opinion about proper child care have shifted from the early 1800s, when maternal associations discussed biblical and secular theories of child rearing, through the 1950s, when books like Spock's Baby and Child Care were widely consulted, to today's era of television advice-givers." "As mothers have increasingly sought assistance in the complex enterprise of raising children, Grant finds, they have become discriminating consumers of professional advice - choosing to follow it, ignore it, or adapt it to their individual circumstances."--Jacket
Fitting their nurture to their nature : the emergence of education for motherhood -- Divine motherhood versus intelligent parenthood : women's organizations and the child-study campaign -- "What is the matter with our children today?" : race, class, and ethnicity in the parent education movement -- Bringing science to the people : delivering the message of scientific motherhood -- Caught between common sense and science : mothers' responses to child development expertise -- Democracy begins at home : the practice and politics of parenting in the 1930s and 1940s -- Dear Doctor : the impact of the baby book on post-World War II mothers.
Includes bibliographical references (pages 251-304) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Mothers -- United States; Motherhood -- United States; Child rearing -- United States; Parenting -- United States; Mothers; Parents; Social psychology; Sociology; Social sciences; Child rearing; Parenting; Mothers; Family Relations; Behavior and Behavior Mechanisms; Parents; Nuclear Family; Psychiatry and Psychology; Family; Persons; Psychology, Social; Named Groups; Sociology; Social Sciences; Anthropology, Education, Sociology and Social Phenomena; Child Rearing; Parenting; United States; Mères -- États-Unis.; Maternité -- États-Unis.; Éducation des enfants -- États-Unis.; Rôle parental -- États-Unis.; Mères.; Parents; Familles; Psychologie sociale; Sociologie; Sciences sociales; Éducation des enfants; Rôle parental; mothers; social psychology; sociology; social sciences; parents; FAMILY & RELATIONSHIPS -- Parenting -- Child Rearing; FAMILY & RELATIONSHIPS -- Parenting -- General; Sociology; Social sciences; Social psychology; Parents; Child rearing; Motherhood; Mothers; Parenting; United States; Moederschap; Opvoedingsondersteuning; Verenigde Staten